+0  
 
0
54
2
avatar

The sequence \((a_n)\) is defined by \(a_1 = \frac{1}{2}\) and \( a_n = a_{n - 1}^2 + a_{n - 1}\) for \(n \ge 2.\) Prove that \(\frac{1}{a_1 + 1} + \frac{1}{a_2 + 1} + \dots + \frac{1}{a_n + 1} < 2\)] for all \(n \ge 1.\)

 

My Work: I wrote the relationship as \(a_n = a_{n - 1} (a_{n - 1} + 1).\) I rearranged this to get \(\frac{1}{a_{n-1}+1}=\frac{1}{a_{n-1}}-\frac{1}{a_n} \quad\)

 

How do I continue? Please explain thoroughly, 'cause I'm thoroughly confused. wink

 Aug 9, 2021
 #1
avatar
0

By the property of telescoping sum, we have quite easily that \dfrac{1}{a_n} = 2-\sum_{k=0}^{n-1}\dfrac{1}{n+a_k}.

 

First we show that a_n<1 which is analogous to proving that \sum_{k=0}^{n-1}\dfrac{1}{n+a_k}<1. Now, we note that \{a_k\} is an increasing sequence, hence a_k\geq a_0 for all k\geq0. This gives \sum_{k=0}^{n-1}\dfrac{1}{n+a_k}\leq\dfrac{n}{n+a_0}=\dfrac{2n}{2n+1}<1 and thus we are done.

 

Now we prove the other part of the inequality. We note that \sum_{k=0}^{n-1}\dfrac{1}{n+a_k}\geq\dfrac{n}{n+a_n} because of increasing property of the sequence a_n. Now using the fact that \dfrac{1}{a_n}=2-\sum_{k=0}^{n-1}\dfrac{1}{n+a_k} we have, after some algebra that 2a_n^2+(n-1)a_n-n\geq0 implying, and keeping in mind that \{a_k\} is a positive sequence, a_n\geq\dfrac{-(n-1)+\sqrt{(n-1)^2+8n}}{4}. It remains to show that this huge quantity is greater than 1-\dfrac{1}{n}. By squaring both sides, and cancelling out terms, we come to 3n>2 which is true for any n. Hence, 1/(a_1 + 1) + 1/(a_2 + 1) + ... + 1/(a_n + 1) < 2.

 Aug 9, 2021
 #2
avatar
+1

Hi, can you explain the property of the telescoping sum, I don't really understand it. Thanks! 

Guest Aug 10, 2021

39 Online Users

avatar
avatar